Establecer como sanción pecuniaria para el delito de peculado, la reparación integral al estado del monto sustraído - Carrera García, Armando Gustavo (2017)
This research work whose theme is "ESTABLISHING AS A PECUNIARY SANCTION FOR THE CRIME OF PECULADO, THE INTEGRAL REPARATION TO THE STATE OF THE AMOUNT SUSTAINED" is so that the objective of this research work is oriented to establish the reparation of the damages caused by part Of the offender in one hundred percent of them. The phenomenon of corruption is an evil that attacks societies worldwide from the so-called underdeveloped countries to countries that are highly developed, and which in recent years has manifested itself with global or regional cases that have drawn much attention to World community by the scale of the economic damages as evidenced in specific cases like FIFA or in South America ODEBRECHT. Ecuador regrettably has not found itself far removed from cases of corruption that have shaken society, criminal behavior that has increased notably in recent years without corruption cases being freely investigated by the Public Prosecutor's Office given the recent reforms to the Code Organic Integral Penal, by requiring as a jurisprudential requirement the previous report of the Comptroller. The problem is evident and is now increasing, I also consider that the causes are multiple because the lack of control is one of the main since the state control agencies do not fully perform their functions which causes in many of the Cases of impunity. In addition to the organizational failures or political or governmental decisions that cause the freedom of public officials for the commission of this type of crime, it should be noted that in the normative field that is what the present investigation will refer to, The penalties provided do not regulate a remedy to the state for the economic damage that has been caused to him, since I consider that, in addition to the custodial sentence, an exception should be applied in this case, in particular, That the injured party in this case the state and therefore society in general does not suffer any deterioration in its assets. The present thesis of Legal Investigation is structured as follows: First, a Conceptual Framework, which includes concepts and definitions, as we have the emulation that is the main topic of our research, as well as other concepts that will give greater emphasis to the proposed topic; A Doctrinal Framework, which covers the doctrines of writers and scholars as to how an equitable penalty can be established for the offense committed in the offense of embezzlement. And a Legal Framework, which includes the analysis of the Constitution of the Republic of Ecuador, the Comprehensive Criminal Organic Code, and then we have a Comparative Legislation, since it served to me to make an analysis of the matter of other countries and to be able to extract the most positive. Secondly the research work comprises a field study in which surveys and interviews are developed to those who know the law in which they help me to determine or contrast the objectives and hypotheses. In the third place after the analysis of the field research, the conclusions and recommendations were made and finally a legal proposal necessary to solve the problem.